Estimation of Phonon Dispersion Relations Using Correlation Effects Among Thermal Displacements of Atoms - Y. Ishikawa; T. Sakuma; T. Hashimoto; Xianglian Xianglian; O. Kamishima; S.A. Danilkin (Atom Indonesia, 2015)
Neutron diffraction measurement of powder α-Fe sample at 295 K was carried out at the high resolution powder diffractometer installed at Japan Proton Accelerator Research Complex (J-PARC). Crystal parameters were determined from Rietveld analysis. The correlation effects among thermal displacements of atoms were estimated from a generalized equation based on the results of fomer diffuse scattering analysis. The force constants among atoms were obtained using an equation for transforming of the correlation effects to force constants. The force constants and the crystal structure of α-Fe were used to estimate the phonon dispersion relations, phonon density of states, and specific heat by computer simulation. The obtained force constants among first-nearest-neighboring atoms is 2.3 eV/Å2 at 295 K and the specific heat is 185 meV/K at 150 K. The calculated phonon dispersion relations and specific heat of α-Fe are similar to those obtained from inelastic neutron scattering and specific heat measurements, respectively. Received: 04 October 2014; Revised: 22 January 2015; Accepted: 30 March 2015